Wild places : Vancouver Island : a kayaking, hiking and recreational guide for Vancouver Island - Kimantas, John (Whitecap Books, 2021)
"A kayaking, hiking and recreational guide for the adventuresome tourist and/ or Vancouver Island resident."--